Analisis Pembaharuan Hukum Pidana Dan Hukum Acara Pidana Dalam Undang-Undang Tindak Pidana Kekerasan Seksual - Moh. Al-vian Zul Khaizar (Universitas Pancasakti Tegal, 2022)
The Act on the Crime of Sexual Violence is a legal umbrella to protect victims of criminal acts of sexual violence. This law has been eagerly awaited by all levels of society given the large number of cases of sexual violence. The Act on the Crime of Sexual Violence is a positive step for the government in dealing with the increasing number of cases of sexual violence in Indonesia. In this study, we will discuss the renewal of criminal law and criminal procedural law in the Criminal Act of Sexual Violence. The type of research used in this research is normative legal research. Normative legal research is research that puts law as a system of norms. The system of norms here is about principles, norms, rules of statutory regulations, court decisions, agreements, and doctrines. In the Act on the Crime of Sexual Violence, there are reforms in aspects of criminal law and criminal procedural law. These reforms aim to complement the Criminal Code and the Criminal Procedure Code. These reforms can also be said to be a deviant aspect of the Criminal Code and the Criminal Procedure Code. However, this is solely to protect the public from criminal acts of sexual violence. In addition, it also aims to enforce a more comprehensive and just law with a more perspective on victims.